Authority of Bawaslu to Handle Violations of Administrative Law in Fiqh Siyasah - Mustakim, Mustakim; Cholidi, Cholidi; Bukhori, KA; Sadi Is, Muhamad; Mohamad, Abdul Basir Bin (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2024)
General Elections a process where individuals carefully choose representatives or candidates who are considered good and appropriate to their preferences. General elections are an important tool in realizing people's sovereignty, which produces people's representatives who represent the aspirations of the people, have quality, and are responsible. The research focused on three main questions: 1. What is Bawaslu's authority in resolving violations of General Election administration law? 2. What factors hinder Bawaslu's authority in addressing violations of General Election administration law? 3. What sanctions apply for violations of General Election administration law?. Library study method was used. Meanwhile, the research results explained that Bawaslu had the authority to resolve violations of general election administration law, including monitoring, handling complaints, investigating, providing recommendations, hearings, campaign assistance, and issuing guidelines. Inhibiting factors for Bawaslu in addressing violations of election administration law in Indonesia include limited resources, legal complexities, authority limitations, non-compliance by parties, political interference, restricted information access, diverse legal cultures, lack of awareness, political party involvement, and time constraints. Meanwhile, the administrative sanctions that Bawaslu could impose on violators of election administration law included cutting campaign budgets, terminating candidacy, as well as recommendations to the General Election Commission.